CN105176079A - Chopped-glass-fiber-reinforced nylon modified material and preparation method thereof - Google Patents
Chopped-glass-fiber-reinforced nylon modified material and preparation method thereof Download PDFInfo
- Publication number
- CN105176079A CN105176079A CN201510588768.XA CN201510588768A CN105176079A CN 105176079 A CN105176079 A CN 105176079A CN 201510588768 A CN201510588768 A CN 201510588768A CN 105176079 A CN105176079 A CN 105176079A
- Authority
- CN
- China
- Prior art keywords
- glass fiber
- resin
- short glass
- fiber reinforced
- temperature
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Granted
Links
Classifications
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L77/00—Compositions of polyamides obtained by reactions forming a carboxylic amide link in the main chain; Compositions of derivatives of such polymers
- C08L77/06—Polyamides derived from polyamines and polycarboxylic acids
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B29—WORKING OF PLASTICS; WORKING OF SUBSTANCES IN A PLASTIC STATE IN GENERAL
- B29C—SHAPING OR JOINING OF PLASTICS; SHAPING OF MATERIAL IN A PLASTIC STATE, NOT OTHERWISE PROVIDED FOR; AFTER-TREATMENT OF THE SHAPED PRODUCTS, e.g. REPAIRING
- B29C2948/00—Indexing scheme relating to extrusion moulding
- B29C2948/92—Measuring, controlling or regulating
- B29C2948/92504—Controlled parameter
- B29C2948/92514—Pressure
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B29—WORKING OF PLASTICS; WORKING OF SUBSTANCES IN A PLASTIC STATE IN GENERAL
- B29C—SHAPING OR JOINING OF PLASTICS; SHAPING OF MATERIAL IN A PLASTIC STATE, NOT OTHERWISE PROVIDED FOR; AFTER-TREATMENT OF THE SHAPED PRODUCTS, e.g. REPAIRING
- B29C2948/00—Indexing scheme relating to extrusion moulding
- B29C2948/92—Measuring, controlling or regulating
- B29C2948/92504—Controlled parameter
- B29C2948/9258—Velocity
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B29—WORKING OF PLASTICS; WORKING OF SUBSTANCES IN A PLASTIC STATE IN GENERAL
- B29C—SHAPING OR JOINING OF PLASTICS; SHAPING OF MATERIAL IN A PLASTIC STATE, NOT OTHERWISE PROVIDED FOR; AFTER-TREATMENT OF THE SHAPED PRODUCTS, e.g. REPAIRING
- B29C2948/00—Indexing scheme relating to extrusion moulding
- B29C2948/92—Measuring, controlling or regulating
- B29C2948/92504—Controlled parameter
- B29C2948/92704—Temperature
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K2201/00—Specific properties of additives
- C08K2201/002—Physical properties
- C08K2201/003—Additives being defined by their diameter
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K2201/00—Specific properties of additives
- C08K2201/002—Physical properties
- C08K2201/004—Additives being defined by their length
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K2201/00—Specific properties of additives
- C08K2201/014—Additives containing two or more different additives of the same subgroup in C08K
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08K—Use of inorganic or non-macromolecular organic substances as compounding ingredients
- C08K2201/00—Specific properties of additives
- C08K2201/017—Additives being an antistatic agent
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L2201/00—Properties
- C08L2201/08—Stabilised against heat, light or radiation or oxydation
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L2205/00—Polymer mixtures characterised by other features
- C08L2205/03—Polymer mixtures characterised by other features containing three or more polymers in a blend
-
- C—CHEMISTRY; METALLURGY
- C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
- C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
- C08L2205/00—Polymer mixtures characterised by other features
- C08L2205/03—Polymer mixtures characterised by other features containing three or more polymers in a blend
- C08L2205/035—Polymer mixtures characterised by other features containing three or more polymers in a blend containing four or more polymers in a blend
Landscapes
- Chemical & Material Sciences (AREA)
- Health & Medical Sciences (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Medicinal Chemistry (AREA)
- Polymers & Plastics (AREA)
- Organic Chemistry (AREA)
- Compositions Of Macromolecular Compounds (AREA)
- Reinforced Plastic Materials (AREA)
Abstract
本发明涉及高分子材料技术领域,具体涉及一种短切玻璃纤维增强尼龙改性材料及其制备方法,所述尼龙改性材料包括如下重量份的原料:PA树脂50-90份、短切玻璃纤维10-50份、稳定剂0.1-0.5份和润滑剂0.1-0.5份。本发明的尼龙改性材料通过加入短切玻璃纤维进行改性,提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性,还大大降低了尼龙改性材料的吸水率和收缩率,具有优良的尺寸稳定性及优异的机械强度。The invention relates to the technical field of polymer materials, in particular to a chopped glass fiber reinforced nylon modified material and a preparation method thereof. The nylon modified material includes the following raw materials in parts by weight: 50-90 parts of PA resin, chopped glass Fiber 10-50 parts, stabilizer 0.1-0.5 parts and lubricant 0.1-0.5 parts. The nylon modified material of the present invention is modified by adding chopped glass fibers, which improves the heat resistance, dimensional stability, rigidity, and mechanical properties such as tensile strength and bending strength of the nylon modified material. The modified material has good wear resistance, heat resistance, oil resistance and chemical resistance, and greatly reduces the water absorption and shrinkage of the nylon modified material, and has excellent dimensional stability and excellent mechanical strength.
Description
技术领域 technical field
本发明涉及高分子材料技术领域,具体涉及一种短切玻璃纤维增强尼龙改性材料及其制备方法。 The invention relates to the technical field of polymer materials, in particular to a chopped glass fiber reinforced nylon modified material and a preparation method thereof.
背景技术 Background technique
尼龙作为工程塑料,与其他塑料相比,有其显著的特点。尼龙是一种半硬质塑料,质地坚韧,有较好的机械性能,特别是耐冲击性能,是其他塑料不可比拟的。它的摩擦系数低,磨耗小,可作自润滑材料,因而可制作传动件。此外,尼龙还具有优良的耐化学腐蚀性、电性能,成型加工方便等优点。但尼龙作为结构件,由于它蠕变性大,耐热性低,收缩率大,尺寸稳定性差,这就限制了尼龙的使用范围。采用玻璃纤维来增强,可以改善上述缺点,扩大使用范围。一般情况下,经玻璃纤维增强后,拉伸强度、弯曲强度提高2~3倍,刚性增加2~5倍,蠕变值降低为未增强的四分之一。 As an engineering plastic, nylon has its remarkable characteristics compared with other plastics. Nylon is a semi-rigid plastic with tough texture and good mechanical properties, especially impact resistance, which is incomparable to other plastics. It has a low coefficient of friction and low wear, and can be used as a self-lubricating material, so it can be used to make transmission parts. In addition, nylon also has the advantages of excellent chemical corrosion resistance, electrical properties, and convenient molding and processing. However, as a structural part, nylon has high creep, low heat resistance, large shrinkage, and poor dimensional stability, which limits the scope of use of nylon. The use of glass fiber for reinforcement can improve the above shortcomings and expand the scope of use. In general, after glass fiber reinforcement, the tensile strength and bending strength are increased by 2 to 3 times, the rigidity is increased by 2 to 5 times, and the creep value is reduced to a quarter of that of unreinforced.
用玻璃纤维与热塑性树脂混合后能提高基体的物理力学性能,其增强效果主要依赖于纤维材料与树脂基体的牢固粘接,使塑料所受负荷能转移到高强度纤维上,并将负荷由局部传递到较大范围甚至于整个物体。玻璃纤维增强尼龙主要有短切玻璃纤维增强和长玻璃纤维增强两种方法,传统的长玻纤(LFT)增强工艺是预浸带工艺,工艺复杂且成本较高,而短切玻璃纤维增强尼龙操作简单,生产效率高,其制备的复合材料性能也较优。 The physical and mechanical properties of the matrix can be improved by mixing glass fibers with thermoplastic resins. The reinforcing effect mainly depends on the firm bonding between the fiber material and the resin matrix, so that the load on the plastic can be transferred to the high-strength fiber, and the load is transferred from the local Transfer to a larger area or even the entire object. Glass fiber reinforced nylon mainly has two methods: chopped glass fiber reinforced and long glass fiber reinforced. The traditional long glass fiber (LFT) reinforced process is a prepreg process, which is complicated and costly, while chopped glass fiber reinforced nylon The operation is simple, the production efficiency is high, and the performance of the prepared composite material is also better.
另外,复合材料中基体与纤维体的界面结合是影响材料性能的重要因素,偶联剂的使用可以明显增强基体与纤维体的界面结合作用,可以很好地提高复合材料的物理性能。 In addition, the interfacial bonding between matrix and fiber in composite materials is an important factor affecting the performance of materials. The use of coupling agents can significantly enhance the interfacial bonding between matrix and fiber, which can well improve the physical properties of composite materials.
发明内容 Contents of the invention
为了克服现有技术中存在的缺点和不足,本发明的目的在于提供一种短切玻璃纤维增强尼龙改性材料,该尼龙改性材料通过加入短切玻璃纤维进行改性,提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性,还大大降低了尼龙改性材料的吸水率和收缩率,具有优良的尺寸稳定性及优异的机械强度。 In order to overcome the disadvantages and deficiencies in the prior art, the object of the present invention is to provide a chopped glass fiber reinforced nylon modified material, which is modified by adding chopped glass fiber to improve the nylon modified material. The material's heat resistance, dimensional stability, rigidity, and mechanical properties such as tensile strength and bending strength have been significantly improved, so that the nylon modified material has good wear resistance, heat resistance, oil resistance and chemical resistance. It also greatly reduces the water absorption and shrinkage of nylon modified materials, and has excellent dimensional stability and excellent mechanical strength.
本发明的另一目的在于提供一种短切玻璃纤维增强尼龙改性材料的制备方法,该制备方法工艺简单,操作控制方便,质量稳定,生产效率高,生产成本低,可大规模工业化生产。 Another object of the present invention is to provide a method for preparing chopped glass fiber reinforced nylon modified material. The preparation method has simple process, convenient operation and control, stable quality, high production efficiency, low production cost, and large-scale industrial production.
本发明的目的通过下述技术方案实现:一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: The purpose of the present invention is achieved through the following technical solutions: a chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂50-90份 PA resin 50-90 parts
短切玻璃纤维10-50份 Chopped glass fiber 10-50 parts
稳定剂0.1-0.5份 Stabilizer 0.1-0.5 parts
润滑剂0.1-0.5份。 Lubricant 0.1-0.5 parts.
本发明的尼龙改性材料通过加入短切玻璃纤维进行改性,提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性,还大大降低了尼龙改性材料的吸水率和收缩率,具有优良的尺寸稳定性及优异的机械强度。 The nylon modified material of the present invention is modified by adding chopped glass fibers, which improves the heat resistance, dimensional stability, rigidity, and mechanical properties such as tensile strength and bending strength of the nylon modified material. The modified material has good wear resistance, heat resistance, oil resistance and chemical resistance, and greatly reduces the water absorption and shrinkage of the nylon modified material, and has excellent dimensional stability and excellent mechanical strength.
优选的,所述PA树脂包括PA6树脂、PA66树脂、PA610树脂和PA1010树脂中的至少一种。更为优选的,所述PA树脂是由PA66树脂和PA6树脂以重量比1-10:1组成的混合物。 Preferably, the PA resin includes at least one of PA6 resin, PA66 resin, PA610 resin and PA1010 resin. More preferably, the PA resin is a mixture of PA66 resin and PA6 resin in a weight ratio of 1-10:1.
本发明通过采用PA66树脂和PA6树脂作为PA树脂复配使用,并控制其重量比为1-10:1,使得尼龙改性材料具有优良的力学强度、耐磨性、自润滑性、耐腐蚀性和较好的加工成型性能。 In the present invention, PA66 resin and PA6 resin are used as PA resin, and the weight ratio is controlled to be 1-10:1, so that the nylon modified material has excellent mechanical strength, wear resistance, self-lubricating property and corrosion resistance. and good processing performance.
优选的,所述PA66树脂为密度在1.10-1.14g/cm3、熔点在250-254℃、平均分子量在10,000-100,000的聚己二酸己二胺。 Preferably, the PA66 resin is polyhexamethylene adipate with a density of 1.10-1.14 g/cm 3 , a melting point of 250-254°C, and an average molecular weight of 10,000-100,000.
本发明通过采用密度在1.10-1.14g/cm3、熔点在250-254℃、平均分子量在10,000-100,000的聚己二酸己二胺,使得尼龙改性材料具有优良的抗张强度、耐韧、耐冲击性和耐磨性佳。 The present invention uses polyhexamethylene adipate with a density of 1.10-1.14g/cm 3 , a melting point of 250-254°C, and an average molecular weight of 10,000-100,000, so that the nylon modified material has excellent tensile strength, toughness and , Good impact resistance and wear resistance.
优选的,所述PA6树脂为密度在1.14-1.18g/cm3、熔点在215-225℃、平均分子量在10,000-100,000的聚己内酰胺。 Preferably, the PA6 resin is polycaprolactam with a density of 1.14-1.18 g/cm 3 , a melting point of 215-225°C, and an average molecular weight of 10,000-100,000.
本发明通过采用密度在1.14-1.18g/cm3、熔点在215-225℃、平均分子量在10,000-100,000的聚己内酰胺作为PA6树脂,使得尼龙改性材料具有优良的热塑性、韧性和耐久性好。 The invention uses polycaprolactam with a density of 1.14-1.18g/cm 3 , a melting point of 215-225°C and an average molecular weight of 10,000-100,000 as the PA6 resin, so that the nylon modified material has excellent thermoplasticity, toughness and durability.
优选的,所述短切玻璃纤维为纤维直径在5-15μm、纤维长度在1-10mm的无碱短切玻璃纤维。 Preferably, the chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 5-15 μm and a fiber length of 1-10 mm.
本发明通过采用纤维直径在5-15μm、纤维长度在1-10mm的无碱短切玻璃纤维作为短切玻璃纤维,提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性。 The invention improves the heat resistance, dimensional stability, rigidity, and tensile strength of the nylon modified material by using alkali-free chopped glass fibers with a fiber diameter of 5-15 μm and a fiber length of 1-10 mm as chopped glass fibers. Mechanical properties such as strength and bending strength have been significantly improved, making nylon modified materials have good wear resistance, heat resistance, oil resistance and chemical resistance.
优选的,所述稳定剂为熔点在270-274℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 Preferably, the stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 270-274°C.
本发明通过采用熔点在270-274℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺作为稳定剂,通过“分子识别”和交链酰胺化与尼龙相容,改善了尼龙改性材料的熔体稳定性,从而改善尼龙改性材料的加工性、降低纤维断丝率、提高产品质量;对尼龙改性材料的光、热、氧化等具有长效稳定作用;可以改善填料和颜料在尼龙改性材料中的分散性。 The present invention uses N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-phthalamide with a melting point of 270-274°C as a stabilizer, through "Molecular recognition" and cross-link amidation are compatible with nylon, which improves the melt stability of nylon modified materials, thereby improving the processability of nylon modified materials, reducing fiber breakage rate, and improving product quality; Light, heat, oxidation, etc. of the material have long-term stabilizing effects; it can improve the dispersion of fillers and pigments in nylon modified materials.
优选的,所述润滑剂包括改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡中的至少一种。更为优选的,所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比0.8-1.2:1.6-2.4:1组成的混合物。 Preferably, the lubricant includes at least one of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax. More preferably, the lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 0.8-1.2:1.6-2.4:1.
本发明通过采用改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡作为润滑剂复配使用,并控制其重量比为0.8-1.2:1.6-2.4:1,氧化聚乙烯蜡是外润滑剂,能降低尼龙改性材料熔体与模具、机筒的摩擦;改性乙烯基双硬脂酰胺和季戊四醇硬脂酸酯是内润滑剂,能降低尼龙改性材料熔体的分子间摩擦;三种润滑剂混合使用可以改善尼龙改性材料在加工过程中的流动性和制品的脱模性。 The present invention uses modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax as lubricant compound, and controls its weight ratio to be 0.8-1.2:1.6-2.4:1, oxidized polyethylene wax It is an external lubricant that can reduce the friction between the nylon modified material melt and the mold and barrel; modified vinyl bisstearamide and pentaerythritol stearate are internal lubricants that can reduce the molecular weight of the nylon modified material melt Inter-friction; the mixed use of the three lubricants can improve the fluidity of the nylon modified material during processing and the mold release of the product.
优选的,所述季戊四醇硬脂酸酯是由羟值在55-65mgKOH/g、熔点在50-60℃的季戊四醇三硬脂酸酯和羟值在25-35mgKOH/g、熔点在55-65℃的季戊四醇四硬脂酸酯以重量比2-3:1组成的混合物。 Preferably, the pentaerythritol stearate is composed of pentaerythritol tristearate with a hydroxyl value of 55-65 mgKOH/g and a melting point of 50-60° C. and a hydroxyl value of 25-35 mgKOH/g and a melting point of 55-65° C. A mixture of pentaerythritol tetrastearate in a weight ratio of 2-3:1.
本发明通过采用羟值在55-65mgKOH/g、熔点在50-60℃的季戊四醇三硬脂酸酯和羟值在25-35mgKOH/g、熔点在55-65℃的季戊四醇四硬脂酸酯作为季戊四醇硬脂酸酯复配使用,并控制其重量比为2-3:1,具有良好的热稳定性和低挥发性,良好的脱模和流动性能,能显著改善尼龙改性材料在高温时的加工性能,提高制品的透明度及表面光洁度。 The present invention uses pentaerythritol tristearate at 55-65mgKOH/g and melting point at 50-60°C and pentaerythritol tetrastearate at 25-35mgKOH/g and melting point at 55-65°C as Pentaerythritol stearate is used in combination, and its weight ratio is controlled to 2-3:1. It has good thermal stability and low volatility, good mold release and flow properties, and can significantly improve the performance of nylon modified materials at high temperatures. Excellent processing performance, improve the transparency and surface finish of the product.
所述尼龙改性材料还包括改性POE树脂3-7份、抗静电剂1-5份、抗氧剂0.5-1.5份、强度改性剂1-5份、增韧改性剂1-5份、抗冲改性剂1-5份。 The nylon modified material also includes 3-7 parts of modified POE resin, 1-5 parts of antistatic agent, 0.5-1.5 parts of antioxidant, 1-5 parts of strength modifier, 1-5 parts of toughening modifier parts, impact modifier 1-5 parts.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在20%-30%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is ethylene with an octene monomer content of 20%-30%. - Octene copolymer.
本发明通过采用聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物作为改性POE树脂,能显著改善材料的常温和低温冲击韧性。本发明通过采用辛烯单体含量在20%-30%的乙烯-辛烯共聚物,能显著提高材料的抗冲击强度和耐热性能,且拉伸强度、撕裂强度等主要力学性能都有很大程度的提高。 The invention adopts the polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin as the modified POE resin, which can significantly improve the impact toughness at room temperature and low temperature of the material. The invention adopts the ethylene-octene copolymer with the octene monomer content of 20%-30%, which can significantly improve the impact strength and heat resistance of the material, and the main mechanical properties such as tensile strength and tear strength are all greatly improved.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比1.4-2.2:1组成的混合物;所述共聚聚丙烯为熔融指数在10-50g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在60-100g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene at a weight ratio of 1.4-2.2:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 10-50 g/10min; the homopolymerized polypropylene Propylene is homopolypropylene with a melt index of 60-100g/10min.
本发明通过采用熔融指数在10-50g/10min的共聚聚丙烯和熔融指数在60-100g/10min的均聚聚丙烯作为聚丙烯复配使用,并控制其重量比为1.4-2.2:1,能显著提高材料的抗冲击强度和热变形温度。 In the present invention, the copolymerized polypropylene with a melt index of 10-50g/10min and the homopolypropylene with a melt index of 60-100g/10min are used as polypropylene, and the weight ratio is controlled to be 1.4-2.2:1, which can Significantly improve the impact strength and heat deflection temperature of the material.
所述抗静电剂是由炭黑和碳纤维以重量比1:1.4-2.2组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:1.4-2.2.
本发明通过采用炭黑和碳纤维作为抗静电剂复配使用,并控制其重量比为1:1.4-2.2,使得改性材料的表面电阻率达到5-7个数量级,在保持材料抗冲击性能的基础上,能显著提高材料的抗静电性能。 In the present invention, carbon black and carbon fiber are used as antistatic agents, and the weight ratio is controlled to be 1:1.4-2.2, so that the surface resistivity of the modified material reaches 5-7 orders of magnitude, while maintaining the impact resistance of the material. On the basis of this, it can significantly improve the antistatic performance of the material.
所述炭黑为比表面积在80-140m3/g、粒径在8-12nm的炭黑;所述碳纤维为长径比在400-600的碳纤维。 The carbon black is carbon black with a specific surface area of 80-140m 3 /g and a particle size of 8-12nm; the carbon fiber is carbon fiber with an aspect ratio of 400-600.
本发明通过采用比表面积在80-140m3/g、粒径在8-12nm的炭黑,能显著提高材料的抗静电性能。本发明通过采用长径比在400-600的碳纤维,能显著提高材料的抗静电性能。 The invention can remarkably improve the antistatic property of the material by adopting the carbon black with a specific surface area of 80-140m 3 /g and a particle diameter of 8-12nm. The invention can remarkably improve the antistatic performance of the material by adopting the carbon fiber with an aspect ratio of 400-600.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:1-2组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1-2.
本发明通过采用抗氧剂1010和抗氧剂168作为抗氧剂复配使用,并控制其重量比为1:1-2,两种抗氧剂均为环保抗氧剂且具有一定的协同作用,可以延缓或抑制材料氧化过程的进行,从而阻止材料的老化并延长其使用寿命。 In the present invention, antioxidant 1010 and antioxidant 168 are used as antioxidant compounds, and their weight ratio is controlled to be 1:1-2. Both antioxidants are environmentally friendly antioxidants and have a certain synergistic effect , can delay or inhibit the oxidation process of the material, thereby preventing the aging of the material and prolonging its service life.
所述强度改性剂是由单丝直径在4-8μm的玄武岩纤维和单丝直径在6-10μm的镁盐晶须以重量比1.6-2.4:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 4-8 μm and magnesium salt whiskers with a single-filament diameter of 6-10 μm at a weight ratio of 1.6-2.4:1.
玄武岩纤维,是玄武岩石料在1450℃~1500℃熔融后,通过铂铑合金拉丝漏板高速拉制而成的连续纤维。类似于玻璃纤维,其性能介于高强度S玻璃纤维和无碱E玻璃纤维之间,玄武岩连续纤维不仅稳定性好,而且还具有电绝缘性、抗腐蚀、抗燃烧、耐高温等多种优异性能。采用玄武岩石料作为强度改性剂,与玻璃纤维相比,具有强度高、冲击强度高、耐温性优良等优点。 Basalt fiber is a continuous fiber drawn at high speed by a platinum-rhodium alloy drawing bushing after melting basalt rock at 1450°C to 1500°C. Similar to glass fiber, its performance is between high-strength S glass fiber and alkali-free E glass fiber. Basalt continuous fiber not only has good stability, but also has many excellent properties such as electrical insulation, corrosion resistance, combustion resistance, and high temperature resistance. performance. Basalt rock is used as the strength modifier, which has the advantages of high strength, high impact strength and excellent temperature resistance compared with glass fiber.
镁盐晶须为单须纤维结构,直径在纳米尺寸范围内,镁盐晶须具有很高的物理机械性能,加入后能增强尼龙材料的强度;而且镁盐晶须易分散,与树脂的相容性好,制得的尼龙产品表面抗划伤能力强、尺寸稳定不易翘曲变形,并能提高尼龙产品的抗老化性能。 Magnesium salt whiskers have a single-whisker fiber structure with a diameter in the range of nanometers. Magnesium salt whiskers have high physical and mechanical properties, and can enhance the strength of nylon materials after being added; Capacitance is good, the surface of the prepared nylon product has strong scratch resistance, stable size, not easy to warp and deform, and can improve the anti-aging performance of nylon product.
本发明通过采用玄武岩纤维和镁盐晶须作为强度改性剂复配使用,并控制其重量比为1.6-2.4:1,可以显著提到尼龙材料的强度。 The present invention uses basalt fiber and magnesium salt whisker as a strength modifier and controls their weight ratio to be 1.6-2.4:1, which can significantly improve the strength of the nylon material.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
本发明通过采用马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体作为增韧改性剂,能显著提高材料的韧性和抗冲击强度。 The invention can remarkably improve the toughness and impact strength of the material by using the vinyl elastomer double-grafted by maleic anhydride and methyl methacrylate as the toughening modifier.
所述抗冲改性剂为分子量在40000-80000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 40,000-80,000.
聚酯型热塑性聚氨酯弹性体具有耐磨性优异、耐臭氧性极好、硬度大、强度高、弹性好、耐低温,有良好的耐油、耐化学药品和耐环境性能等优点。 Polyester thermoplastic polyurethane elastomer has excellent wear resistance, excellent ozone resistance, high hardness, high strength, good elasticity, low temperature resistance, good oil resistance, chemical resistance and environmental resistance.
本发明通过采用分子量在40000-80000的聚酯型热塑性聚氨酯弹性体作为抗冲改性剂,可以提高材料的抗冲击性能,还可以降低材料的熔融粘度、提高流动性、改善塑料的加工性能,提高材料的耐腐蚀性、刚性、阻燃性、电绝缘性、耐热性和成型加工性。 The invention adopts the polyester thermoplastic polyurethane elastomer with a molecular weight of 40,000-80,000 as the impact modifier, which can improve the impact resistance of the material, reduce the melt viscosity of the material, improve the fluidity, and improve the processing performance of the plastic. Improve corrosion resistance, rigidity, flame retardancy, electrical insulation, heat resistance and formability of materials.
本发明的另一目的通过下述技术方案实现:一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: Another object of the present invention is achieved through the following technical solutions: a preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混5-10min,得到混合物; (1) Weigh the raw materials except chopped glass fiber according to the weight ratio, add them to the high-speed mixer and mix them for 5-10 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,挤出机的工艺参数为:一区温度210-250℃,二区温度210-250℃,三区温度210-250℃,四区温度210-250℃,五区温度210-250℃,六区温度210-250℃,七区温度210-240℃,八区温度210-240℃,九区温度210-240℃,模头温度210-230℃,压力18-23Mpa,螺杆转速350-450r/min。 In the step (2), the process parameters of the extruder are: the temperature of the first zone is 210-250°C, the temperature of the second zone is 210-250°C, the temperature of the third zone is 210-250°C, the temperature of the fourth zone is 210-250°C, and the temperature of the fifth zone is 210-250°C. The temperature is 210-250℃, the temperature in the sixth zone is 210-250℃, the temperature in the seventh zone is 210-240℃, the temperature in the eighth zone is 210-240℃, the temperature in the ninth zone is 210-240℃, the temperature of the die head is 210-230℃, the pressure is 18-23Mpa , screw speed 350-450r/min.
本发明的制备方法工艺简单,操作控制方便,质量稳定,生产效率高,生产成本低,可大规模工业化生产。 The preparation method of the invention has the advantages of simple process, convenient operation and control, stable quality, high production efficiency, low production cost and large-scale industrial production.
本发明的有益效果在于:本发明的尼龙改性材料通过加入短切玻璃纤维进行改性,提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性,还大大降低了尼龙改性材料的吸水率和收缩率,具有优良的尺寸稳定性及优异的机械强度。 The beneficial effect of the present invention is that: the nylon modified material of the present invention is modified by adding chopped glass fibers, which improves the heat resistance, dimensional stability, rigidity, and mechanical properties such as tensile strength and bending strength of the nylon modified material. The performance has been significantly improved, so that the nylon modified material has good wear resistance, heat resistance, oil resistance and chemical resistance, and also greatly reduces the water absorption and shrinkage of the nylon modified material, and has excellent dimensional stability. and excellent mechanical strength.
本发明的制备方法工艺简单,操作控制方便,质量稳定,生产效率高,生产成本低,可大规模工业化生产。 The preparation method of the invention has the advantages of simple process, convenient operation and control, stable quality, high production efficiency, low production cost and large-scale industrial production.
具体实施方式 Detailed ways
为了便于本领域技术人员的理解,下面结合实施例对本发明作进一步的说明,实施方式提及的内容并非对本发明的限定。 In order to facilitate the understanding of those skilled in the art, the present invention will be further described below in conjunction with the examples, and the contents mentioned in the embodiments are not intended to limit the present invention.
实施例1 Example 1
一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: A chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂50份 PA resin 50 parts
短切玻璃纤维10份 10 parts chopped glass fiber
稳定剂0.1份 Stabilizer 0.1 part
润滑剂0.1份。 Lubricant 0.1 part.
所述PA树脂是由PA66树脂和PA6树脂以重量比1:1组成的混合物。 The PA resin is a mixture of PA66 resin and PA6 resin with a weight ratio of 1:1.
所述PA66树脂为密度在1.10g/cm3、熔点在250℃、平均分子量在10,000的聚己二酸己二胺。 The PA66 resin is polyhexamethylene adipate with a density of 1.10 g/cm 3 , a melting point of 250° C. and an average molecular weight of 10,000.
所述PA6树脂为密度在1.14g/cm3、熔点在215℃、平均分子量在10,000的聚己内酰胺。 The PA6 resin is polycaprolactam with a density of 1.14g/cm 3 , a melting point of 215°C and an average molecular weight of 10,000.
所述短切玻璃纤维为纤维直径在5μm、纤维长度在1mm的无碱短切玻璃纤维。 The chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 5 μm and a fiber length of 1 mm.
所述稳定剂为熔点在270℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 The stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 270°C.
所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比0.8:1.6:1组成的混合物。 The lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 0.8:1.6:1.
所述季戊四醇硬脂酸酯是由羟值在55mgKOH/g、熔点在50℃的季戊四醇三硬脂酸酯和羟值在25mgKOH/g、熔点在55℃的季戊四醇四硬脂酸酯以重量比2:1组成的混合物。 Described pentaerythritol stearate is at 55mgKOH/g, the pentaerythritol tristearate of fusing point at 50 ℃ and the pentaerythritol tetrastearate at 55 ℃ with hydroxyl value at 25mgKOH/g, fusing point in weight ratio 2 : 1 composition of the mixture.
一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: A preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混5min,得到混合物; (1) Weigh the raw materials except chopped glass fiber according to the weight ratio, add them to the high-speed mixer and mix them for 5 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,双螺杆挤出机的工艺参数为:一区温度210℃,二区温度210℃,三区温度210℃,四区温度210℃,五区温度210℃,六区温度210℃,七区温度210℃,八区温度210℃,九区温度210℃,模头温度210℃,压力18Mpa,螺杆转速350r/min。 In the step (2), the process parameters of the twin-screw extruder are: the temperature of the first zone is 210°C, the temperature of the second zone is 210°C, the temperature of the third zone is 210°C, the temperature of the fourth zone is 210°C, the temperature of the fifth zone is 210°C, and the temperature of the sixth zone is 210°C. The temperature is 210°C, the temperature of the seventh zone is 210°C, the temperature of the eighth zone is 210°C, the temperature of the ninth zone is 210°C, the temperature of the die head is 210°C, the pressure is 18Mpa, and the screw speed is 350r/min.
实施例2 Example 2
一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: A chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂60份 PA resin 60 parts
短切玻璃纤维20份 20 parts chopped glass fiber
稳定剂0.2份 Stabilizer 0.2 parts
润滑剂0.2份。 0.2 parts of lubricant.
所述PA树脂是由PA66树脂和PA6树脂以重量比3:1组成的混合物。 The PA resin is a mixture of PA66 resin and PA6 resin in a weight ratio of 3:1.
所述PA66树脂为密度在1.11g/cm3、熔点在251℃、平均分子量在30,000的聚己二酸己二胺。 The PA66 resin is polyhexamethylene adipate with a density of 1.11 g/cm 3 , a melting point of 251° C. and an average molecular weight of 30,000.
所述PA6树脂为密度在1.15g/cm3、熔点在218℃、平均分子量在30,000的聚己内酰胺。 The PA6 resin is polycaprolactam with a density of 1.15g/cm 3 , a melting point of 218°C and an average molecular weight of 30,000.
所述短切玻璃纤维为纤维直径在8μm、纤维长度在3mm的无碱短切玻璃纤维。 The chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 8 μm and a fiber length of 3 mm.
所述稳定剂为熔点在271℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 The stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 271°C.
所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比0.9:1.8:1组成的混合物。 The lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 0.9:1.8:1.
所述季戊四醇硬脂酸酯是由羟值在58mgKOH/g、熔点在52℃的季戊四醇三硬脂酸酯和羟值在28mgKOH/g、熔点在58℃的季戊四醇四硬脂酸酯以重量比2.2:1组成的混合物。 Described pentaerythritol stearate is by the pentaerythritol tristearate and hydroxyl value at 28mgKOH/g, the pentaerythritol tetrastearate of melting point at 52 ℃ by weight ratio 2.2 at 58mgKOH/g, fusing point. : 1 composition of the mixture.
一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: A preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混6min,得到混合物; (1) Weigh the raw materials except chopped glass fiber according to the weight ratio, add them to the high-speed mixer and mix them for 6 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,双螺杆挤出机的工艺参数为:一区温度220℃,二区温度220℃,三区温度220℃,四区温度220℃,五区温度220℃,六区温度220℃,七区温度218℃,八区温度218℃,九区温度218℃,模头温度215℃,压力20Mpa,螺杆转速380r/min。 In the step (2), the process parameters of the twin-screw extruder are: the temperature of the first zone is 220°C, the temperature of the second zone is 220°C, the temperature of the third zone is 220°C, the temperature of the fourth zone is 220°C, the temperature of the fifth zone is 220°C, and the temperature of the sixth zone is 220°C. The temperature is 220°C, the temperature in the seventh zone is 218°C, the temperature in the eighth zone is 218°C, the temperature in the ninth zone is 218°C, the temperature of the die head is 215°C, the pressure is 20Mpa, and the screw speed is 380r/min.
实施例3 Example 3
一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: A chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂70份 PA resin 70 parts
短切玻璃纤维30份 Chopped glass fiber 30 parts
稳定剂0.3份 Stabilizer 0.3 parts
润滑剂0.3份。 0.3 parts of lubricant.
所述PA树脂是由PA66树脂和PA6树脂以重量比5:1组成的混合物。 The PA resin is a mixture of PA66 resin and PA6 resin in a weight ratio of 5:1.
所述PA66树脂为密度在1.12g/cm3、熔点在252℃、平均分子量在50,000的聚己二酸己二胺。 The PA66 resin is polyhexamethylene adipate with a density of 1.12 g/cm 3 , a melting point of 252° C. and an average molecular weight of 50,000.
所述PA6树脂为密度在1.16g/cm3、熔点在220℃、平均分子量在50,000的聚己内酰胺。 The PA6 resin is polycaprolactam with a density of 1.16 g/cm 3 , a melting point of 220° C. and an average molecular weight of 50,000.
所述短切玻璃纤维为纤维直径在10μm、纤维长度在5mm的无碱短切玻璃纤维。 The chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 10 μm and a fiber length of 5 mm.
所述稳定剂为熔点在272℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 The stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 272°C.
所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比1:2:1组成的混合物。 The lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 1:2:1.
所述季戊四醇硬脂酸酯是由羟值在60mgKOH/g、熔点在55℃的季戊四醇三硬脂酸酯和羟值在30mgKOH/g、熔点在60℃的季戊四醇四硬脂酸酯以重量比2.5:1组成的混合物。 Described pentaerythritol stearate is at 60mgKOH/g, the pentaerythritol tristearate of fusing point at 55 ℃ and the pentaerythritol tetrastearate at 60 ℃ with hydroxyl value at 30mgKOH/g, fusing point in weight ratio 2.5 : 1 composition of the mixture.
一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: A preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混8min,得到混合物; (1) Weigh the raw materials except chopped glass fiber according to the weight ratio, add them to the high-speed mixer and mix them for 8 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,双螺杆挤出机的工艺参数为:一区温度230℃,二区温度230℃,三区温度230℃,四区温度230℃,五区温度230℃,六区温度230℃,七区温度225℃,八区温度225℃,九区温度225℃,模头温度2120℃,压力20Mpa,螺杆转速400r/min。 In the step (2), the process parameters of the twin-screw extruder are: the temperature of the first zone is 230°C, the temperature of the second zone is 230°C, the temperature of the third zone is 230°C, the temperature of the fourth zone is 230°C, the temperature of the fifth zone is 230°C, and the temperature of the sixth zone is 230°C. The temperature is 230°C, the temperature in the seventh zone is 225°C, the temperature in the eighth zone is 225°C, the temperature in the ninth zone is 225°C, the temperature of the die head is 2120°C, the pressure is 20Mpa, and the screw speed is 400r/min.
实施例4 Example 4
一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: A chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂80份 PA resin 80 parts
短切玻璃纤维40份 Chopped glass fiber 40 parts
稳定剂0.4份 Stabilizer 0.4 parts
润滑剂0.4份。 0.4 parts of lubricant.
所述PA树脂是由PA66树脂和PA6树脂以重量比8:1组成的混合物。 The PA resin is a mixture of PA66 resin and PA6 resin in a weight ratio of 8:1.
所述PA66树脂为密度在1.13g/cm3、熔点在253℃、平均分子量在80,000的聚己二酸己二胺。 The PA66 resin is polyhexamethylene adipate with a density of 1.13 g/cm 3 , a melting point of 253° C. and an average molecular weight of 80,000.
所述PA6树脂为密度在1.17g/cm3、熔点在222℃、平均分子量在80,000的聚己内酰胺。 The PA6 resin is polycaprolactam with a density of 1.17g/cm 3 , a melting point of 222°C and an average molecular weight of 80,000.
所述短切玻璃纤维为纤维直径在12μm、纤维长度在8mm的无碱短切玻璃纤维。 The chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 12 μm and a fiber length of 8 mm.
所述稳定剂为熔点在273℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 The stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 273°C.
所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比1.1:2.2:1组成的混合物。 The lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 1.1:2.2:1.
所述季戊四醇硬脂酸酯是由羟值在62mgKOH/g、熔点在58℃的季戊四醇三硬脂酸酯和羟值在32mgKOH/g、熔点在62℃的季戊四醇四硬脂酸酯以重量比2.8:1组成的混合物。 Described pentaerythritol stearate is by the pentaerythritol tristearate and hydroxyl value at 32mgKOH/g, the pentaerythritol tetrastearate of melting point at 58 ℃ by weight ratio 2.8 at 62mgKOH/g, fusing point. : 1 composition of the mixture.
一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: A preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混9min,得到混合物; (1) Weigh the raw materials except chopped glass fiber according to the weight ratio, add them to the high-speed mixer and blend for 9 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,双螺杆挤出机的工艺参数为:一区温度240℃,二区温度240℃,三区温度240℃,四区温度240℃,五区温度240℃,六区温度240℃,七区温度232℃,八区温度232℃,九区温度232℃,模头温度225℃,压力22Mpa,螺杆转速420r/min。 In the step (2), the process parameters of the twin-screw extruder are: the temperature of the first zone is 240°C, the temperature of the second zone is 240°C, the temperature of the third zone is 240°C, the temperature of the fourth zone is 240°C, the temperature of the fifth zone is 240°C, and the temperature of the sixth zone is 240°C. The temperature is 240°C, the temperature in the seventh zone is 232°C, the temperature in the eighth zone is 232°C, the temperature in the ninth zone is 232°C, the temperature of the die head is 225°C, the pressure is 22Mpa, and the screw speed is 420r/min.
实施例5 Example 5
一种短切玻璃纤维增强尼龙改性材料,所述尼龙改性材料包括如下重量份的原料: A chopped glass fiber reinforced nylon modified material, the nylon modified material includes the following raw materials in parts by weight:
PA树脂90份 PA resin 90 parts
短切玻璃纤维50份 Chopped glass fiber 50 parts
稳定剂0.5份 Stabilizer 0.5 parts
润滑剂0.5份。 0.5 parts of lubricant.
所述PA树脂是由PA66树脂和PA6树脂以重量比10:1组成的混合物。 The PA resin is a mixture of PA66 resin and PA6 resin with a weight ratio of 10:1.
所述PA66树脂为密度在1.14g/cm3、熔点在254℃、平均分子量在100,000的聚己二酸己二胺。 The PA66 resin is polyhexamethylene adipate with a density of 1.14 g/cm 3 , a melting point of 254° C. and an average molecular weight of 100,000.
所述PA6树脂为密度在1.18g/cm3、熔点在225℃、平均分子量在100,000的聚己内酰胺。 The PA6 resin is polycaprolactam with a density of 1.18g/cm 3 , a melting point of 225°C and an average molecular weight of 100,000.
所述短切玻璃纤维为纤维直径在15μm、纤维长度在10mm的无碱短切玻璃纤维。 The chopped glass fiber is an alkali-free chopped glass fiber with a fiber diameter of 15 μm and a fiber length of 10 mm.
所述稳定剂为熔点在274℃的N,N’-双(2,2,6,6-四甲基-4-哌啶基)-1,3-苯二甲酰胺。 The stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide with a melting point of 274°C.
所述润滑剂是由改性乙烯基双硬脂酰胺、季戊四醇硬脂酸酯和氧化聚乙烯蜡以重量比1.2:2.4:1组成的混合物。 The lubricant is a mixture composed of modified vinyl bis stearamide, pentaerythritol stearate and oxidized polyethylene wax in a weight ratio of 1.2:2.4:1.
所述季戊四醇硬脂酸酯是由羟值在65mgKOH/g、熔点在60℃的季戊四醇三硬脂酸酯和羟值在35mgKOH/g、熔点在65℃的季戊四醇四硬脂酸酯以重量比3:1组成的混合物。 Described pentaerythritol stearate is at 65mgKOH/g, the pentaerythritol tristearate of fusing point at 60 ℃ and the pentaerythritol tetrastearate at 65 ℃ with hydroxyl value at 35mgKOH/g, fusing point in weight ratio 3 : 1 composition of the mixture.
一种短切玻璃纤维增强尼龙改性材料的制备方法,包括如下步骤: A preparation method of chopped glass fiber reinforced nylon modified material, comprising the steps of:
(1)按重量配比称取除短切玻璃纤维以外的原料,加入到高速混料机中共混10min,得到混合物; (1) Weigh the raw materials other than chopped glass fiber according to the weight ratio, add them to the high-speed mixer and mix them for 10 minutes to obtain the mixture;
(2)将步骤(1)共混得到的混合物加入到挤出机挤出,按重量配比称取短切玻璃纤维从挤出机的侧喂料口加入; (2) Add the mixture obtained by blending in step (1) to the extruder for extrusion, weigh the chopped glass fiber according to the weight ratio and add it from the side feeding port of the extruder;
(3)将步骤(2)挤出后的材料经冷却、切粒和筛选,制得所述尼龙改性材料; (3) cooling, pelletizing and screening the material extruded in step (2) to obtain the nylon modified material;
所述步骤(2)中,双螺杆挤出机的工艺参数为:一区温度250℃,二区温度250℃,三区温度250℃,四区温度250℃,五区温度250℃,六区温度250℃,七区温度240℃,八区温度240℃,九区温度240℃,模头温度230℃,压力23Mpa,螺杆转速450r/min。 In the step (2), the process parameters of the twin-screw extruder are: the temperature of the first zone is 250°C, the temperature of the second zone is 250°C, the temperature of the third zone is 250°C, the temperature of the fourth zone is 250°C, the temperature of the fifth zone is 250°C, and the temperature of the sixth zone is 250°C. The temperature is 250°C, the temperature of the seventh zone is 240°C, the temperature of the eighth zone is 240°C, the temperature of the ninth zone is 240°C, the temperature of the die head is 230°C, the pressure is 23Mpa, and the screw speed is 450r/min.
实施例6 Example 6
本实施例于上述实施例1的不同之处在于: The difference between this embodiment and above-mentioned embodiment 1 is:
所述尼龙改性材料还包括改性POE树脂3份、抗静电剂1份、抗氧剂0.5份、强度改性剂1份、增韧改性剂1份、抗冲改性剂1份。 The nylon modified material also includes 3 parts of modified POE resin, 1 part of antistatic agent, 0.5 part of antioxidant, 1 part of strength modifier, 1 part of toughening modifier and 1 part of impact modifier.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在20%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is an ethylene-octene copolymer with an octene monomer content of 20%. copolymer.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比1.4:1组成的混合物;所述共聚聚丙烯为熔融指数在10g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在60g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene with a weight ratio of 1.4:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 10g/10min; the homopolymerized polypropylene is a melt index Homopolypropylene at 60g/10min.
所述抗静电剂是由炭黑和碳纤维以重量比1:1.4组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:1.4.
所述炭黑为比表面积在800m3/g、粒径在8nm的炭黑;所述碳纤维为长径比在400的碳纤维。 The carbon black is a carbon black with a specific surface area of 800m 3 /g and a particle size of 8nm; the carbon fiber is a carbon fiber with an aspect ratio of 400.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:1组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.
所述强度改性剂是由单丝直径在4μm的玄武岩纤维和单丝直径在6μm的镁盐晶须以重量比1.6:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 4 μm and magnesium salt whiskers with a single-filament diameter of 6 μm at a weight ratio of 1.6:1.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
所述抗冲改性剂为分子量在40000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 40,000.
实施例7 Example 7
本实施例于上述实施例2的不同之处在于: The difference between this embodiment and above-mentioned embodiment 2 is:
所述尼龙改性材料还包括改性POE树脂4份、抗静电剂2份、抗氧剂0.8份、强度改性剂2份、增韧改性剂2份、抗冲改性剂2份。 The nylon modified material also includes 4 parts of modified POE resin, 2 parts of antistatic agent, 0.8 parts of antioxidant, 2 parts of strength modifier, 2 parts of toughening modifier and 2 parts of impact modifier.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在22%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is ethylene-octene with an octene monomer content of 22%. copolymer.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比1.6:1组成的混合物;所述共聚聚丙烯为熔融指数在20g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在70g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene with a weight ratio of 1.6:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 20g/10min; the homopolymerized polypropylene is a melt index Homopolypropylene at 70g/10min.
所述抗静电剂是由炭黑和碳纤维以重量比1:1.6组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:1.6.
所述炭黑为比表面积在100m3/g、粒径在9nm的炭黑;所述碳纤维为长径比在450的碳纤维。 The carbon black is carbon black with a specific surface area of 100m 3 /g and a particle size of 9nm; the carbon fiber is a carbon fiber with an aspect ratio of 450.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:1.2组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.2.
所述强度改性剂是由单丝直径在4~8μm的玄武岩纤维和单丝直径在7μm的镁盐晶须以重量比1.8:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 4-8 μm and magnesium salt whiskers with a single-filament diameter of 7 μm at a weight ratio of 1.8:1.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
所述抗冲改性剂为分子量在50000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 50,000.
实施例8 Example 8
本实施例于上述实施例3的不同之处在于: The difference between this embodiment and above-mentioned embodiment 3 is:
所述尼龙改性材料还包括改性POE树脂5份、抗静电剂3份、抗氧剂1份、强度改性剂3份、增韧改性剂3份、抗冲改性剂3份。 The nylon modified material also includes 5 parts of modified POE resin, 3 parts of antistatic agent, 1 part of antioxidant, 3 parts of strength modifier, 3 parts of toughening modifier and 3 parts of impact modifier.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在25%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is an ethylene-octene copolymer with an octene monomer content of 25%. copolymer.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比1.8:1组成的混合物;所述共聚聚丙烯为熔融指数在30g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在80g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene with a weight ratio of 1.8:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 30g/10min; the homopolymerized polypropylene is a melt index Homopolypropylene at 80g/10min.
所述抗静电剂是由炭黑和碳纤维以重量比1:1.8组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:1.8.
所述炭黑为比表面积在110m3/g、粒径在10nm的炭黑;所述碳纤维为长径比在500的碳纤维。 The carbon black is a carbon black with a specific surface area of 110m 3 /g and a particle size of 10nm; the carbon fiber is a carbon fiber with an aspect ratio of 500.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:1.5组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.5.
所述强度改性剂是由单丝直径在6μm的玄武岩纤维和单丝直径在8μm的镁盐晶须以重量比2:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 6 μm and magnesium salt whiskers with a single-filament diameter of 8 μm at a weight ratio of 2:1.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
所述抗冲改性剂为分子量在60000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 60,000.
实施例9 Example 9
本实施例于上述实施例4的不同之处在于: The difference between this embodiment and above-mentioned embodiment 4 is:
所述尼龙改性材料还包括改性POE树脂6份、抗静电剂4份、抗氧剂1.2份、强度改性剂4份、增韧改性剂4份、抗冲改性剂4份。 The nylon modified material also includes 6 parts of modified POE resin, 4 parts of antistatic agent, 1.2 parts of antioxidant, 4 parts of strength modifier, 4 parts of toughening modifier and 4 parts of impact modifier.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在28%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is ethylene-octene with an octene monomer content of 28%. copolymer.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比2:1组成的混合物;所述共聚聚丙烯为熔融指数在40g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在90g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene at a weight ratio of 2:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 40 g/10min; the homopolymerized polypropylene is a melt index Homopolypropylene at 90g/10min.
所述抗静电剂是由炭黑和碳纤维以重量比1:2组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:2.
所述炭黑为比表面积在120m3/g、粒径在11nm的炭黑;所述碳纤维为长径比在550的碳纤维。 The carbon black is a carbon black with a specific surface area of 120m 3 /g and a particle size of 11nm; the carbon fiber is a carbon fiber with an aspect ratio of 550.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:1.8组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.8.
所述强度改性剂是由单丝直径在7μm的玄武岩纤维和单丝直径在9μm的镁盐晶须以重量比2.2:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 7 μm and magnesium salt whiskers with a single-filament diameter of 9 μm at a weight ratio of 2.2:1.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
所述抗冲改性剂为分子量在70000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 70,000.
实施例10 Example 10
本实施例于上述实施例5的不同之处在于: The difference between this embodiment and above-mentioned embodiment 5 is:
所述尼龙改性材料还包括改性POE树脂7份、抗静电剂5份、抗氧剂1.5份、强度改性剂5份、增韧改性剂5份、抗冲改性剂5份。 The nylon modified material also includes 7 parts of modified POE resin, 5 parts of antistatic agent, 1.5 parts of antioxidant, 5 parts of strength modifier, 5 parts of toughening modifier and 5 parts of impact modifier.
所述改性POE树脂为聚丙烯和POE树脂共混改性得到的聚丙烯/乙烯-辛烯共聚物;所述乙烯-辛烯共聚物为辛烯单体含量在30%的乙烯-辛烯共聚物。 The modified POE resin is a polypropylene/ethylene-octene copolymer obtained by blending and modifying polypropylene and POE resin; the ethylene-octene copolymer is an ethylene-octene copolymer with an octene monomer content of 30%. copolymer.
所述聚丙烯是有共聚聚丙烯和均聚聚丙烯以重量比2.2:1组成的混合物;所述共聚聚丙烯为熔融指数在50g/10min的共聚聚丙烯;所述均聚聚丙烯为熔融指数在100g/10min的均聚聚丙烯。 The polypropylene is a mixture of copolymerized polypropylene and homopolypropylene with a weight ratio of 2.2:1; the copolymerized polypropylene is a copolymerized polypropylene with a melt index of 50 g/10min; the homopolymerized polypropylene is a melt index Homopolypropylene at 100g/10min.
所述抗静电剂是由炭黑和碳纤维以重量比1:2.2组成的混合物。 The antistatic agent is a mixture of carbon black and carbon fiber in a weight ratio of 1:2.2.
所述炭黑为比表面积在140m3/g、粒径在12nm的炭黑;所述碳纤维为长径比在600的碳纤维。 The carbon black is carbon black with a specific surface area of 140m 3 /g and a particle size of 12nm; the carbon fiber is a carbon fiber with an aspect ratio of 600.
所述抗氧剂是由抗氧剂1010和抗氧剂168以重量比1:2组成的混合物。 The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:2.
所述强度改性剂是由单丝直径在8μm的玄武岩纤维和单丝直径在10μm的镁盐晶须以重量比2.4:1组成的混合物。 The strength modifier is a mixture composed of basalt fibers with a single-filament diameter of 8 μm and magnesium salt whiskers with a single-filament diameter of 10 μm at a weight ratio of 2.4:1.
所述增韧改性剂为马来酸酐和甲基丙烯酸甲酯双接枝的乙烯类弹性体。 The toughening modifier is vinyl elastomer double-grafted with maleic anhydride and methyl methacrylate.
所述抗冲改性剂为分子量在80000的聚酯型热塑性聚氨酯弹性体。 The impact modifier is a polyester thermoplastic polyurethane elastomer with a molecular weight of 80,000.
实施例1-10制得的短切玻璃纤维增强尼龙改性材料的机械物理性能如表1所示。 The mechanical and physical properties of the chopped glass fiber reinforced nylon modified material prepared in Examples 1-10 are shown in Table 1.
表1 Table 1
从表1可以看出,本发明制得的短切玻璃纤维增强尼龙改性材料通过加入短切玻璃纤维提高了尼龙改性材料的耐热性,尺寸稳定性,刚性,且拉伸强度和弯曲强度等机械性能有明显提高,使尼龙改性材料具有良好的耐磨性、耐热性、耐油性及耐化学药品性,还大大降低了尼龙改性材料的吸水率和收缩率,具有优良的尺寸稳定性及优异的机械强度。 As can be seen from Table 1, the chopped glass fiber reinforced nylon modified material prepared by the present invention has improved the heat resistance of the nylon modified material by adding chopped glass fiber, dimensional stability, rigidity, and tensile strength and bending The strength and other mechanical properties have been significantly improved, so that the nylon modified material has good wear resistance, heat resistance, oil resistance and chemical resistance, and it also greatly reduces the water absorption and shrinkage of the nylon modified material. Dimensional stability and excellent mechanical strength.
上述实施例为本发明较佳的实现方案,除此之外,本发明还可以其它方式实现,在不脱离本发明构思的前提下任何显而易见的替换均在本发明的保护范围之内。 The above-mentioned embodiments are preferred implementation solutions of the present invention. In addition, the present invention can also be realized in other ways, and any obvious replacements are within the protection scope of the present invention without departing from the concept of the present invention.
Claims (10)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201510588768.XA CN105176079B (en) | 2015-09-16 | 2015-09-16 | A kind of short glass fiber enhancing modified nylon material and preparation method thereof |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201510588768.XA CN105176079B (en) | 2015-09-16 | 2015-09-16 | A kind of short glass fiber enhancing modified nylon material and preparation method thereof |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN105176079A true CN105176079A (en) | 2015-12-23 |
| CN105176079B CN105176079B (en) | 2018-10-23 |
Family
ID=54898542
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201510588768.XA Active CN105176079B (en) | 2015-09-16 | 2015-09-16 | A kind of short glass fiber enhancing modified nylon material and preparation method thereof |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN105176079B (en) |
Cited By (12)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN105949752A (en) * | 2016-05-11 | 2016-09-21 | 南京京锦元科技实业有限公司 | Glass fiber reinforced polyamide resin composite |
| CN108165001A (en) * | 2017-12-25 | 2018-06-15 | 江苏金发科技新材料有限公司 | The good appearance polyamide compoiste material of low water absorption |
| CN111205637A (en) * | 2018-11-21 | 2020-05-29 | 杭州本松新材料技术股份有限公司 | Heat stabilizer and composite material comprising the same |
| CN111363347A (en) * | 2020-03-19 | 2020-07-03 | 宁波创力液压机械制造有限公司 | Glass fiber reinforced nylon composite material and preparation method thereof |
| CN111892813A (en) * | 2020-07-28 | 2020-11-06 | 横店集团得邦工程塑料有限公司 | Low-odor reinforced toughened flame-retardant PA6 composite material and preparation method thereof |
| CN112266607A (en) * | 2020-09-30 | 2021-01-26 | 南京聚隆科技股份有限公司 | Heat-resistant glass fiber reinforced nylon material and preparation method thereof |
| CN112409668A (en) * | 2020-10-20 | 2021-02-26 | 浙江德裕科技有限公司 | Plastic window rail and preparation method thereof |
| CN112592577A (en) * | 2020-12-14 | 2021-04-02 | 山东明珠材料科技有限公司 | Continuous preparation method of glass fiber reinforced polyurethane section |
| CN113667300A (en) * | 2021-09-14 | 2021-11-19 | 四川恒领皓睿塑胶科技有限公司 | Glass fiber reinforced engineering plastic and preparation method thereof |
| CN113773458A (en) * | 2021-09-14 | 2021-12-10 | 安徽华超新材料科技有限公司 | Modification treatment method of chopped glass fibers |
| CN114507439A (en) * | 2022-01-11 | 2022-05-17 | 宁波帅特龙集团有限公司 | Efficient antifouling nylon 6/glass fiber composite material and preparation method thereof |
| CN114507441A (en) * | 2021-12-24 | 2022-05-17 | 金发科技股份有限公司 | Polyamide composite material and preparation method and application thereof |
Citations (4)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN102061088A (en) * | 2010-12-10 | 2011-05-18 | 南京聚隆科技股份有限公司 | Nylon engineering plastics for high-speed transit railway track and manufacture method thereof |
| CN102675863A (en) * | 2012-05-11 | 2012-09-19 | 金发科技股份有限公司 | Low warpage polyamide composite material |
| CN103146187A (en) * | 2013-03-29 | 2013-06-12 | 大河宝利材料科技(苏州)有限公司 | Polyamide composite material as well as preparation method and use thereof |
| CN103849138A (en) * | 2012-11-29 | 2014-06-11 | 合肥杰事杰新材料股份有限公司 | Chopped glass fiber reinforced nylon composite material and preparation method thereof |
-
2015
- 2015-09-16 CN CN201510588768.XA patent/CN105176079B/en active Active
Patent Citations (4)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN102061088A (en) * | 2010-12-10 | 2011-05-18 | 南京聚隆科技股份有限公司 | Nylon engineering plastics for high-speed transit railway track and manufacture method thereof |
| CN102675863A (en) * | 2012-05-11 | 2012-09-19 | 金发科技股份有限公司 | Low warpage polyamide composite material |
| CN103849138A (en) * | 2012-11-29 | 2014-06-11 | 合肥杰事杰新材料股份有限公司 | Chopped glass fiber reinforced nylon composite material and preparation method thereof |
| CN103146187A (en) * | 2013-03-29 | 2013-06-12 | 大河宝利材料科技(苏州)有限公司 | Polyamide composite material as well as preparation method and use thereof |
Non-Patent Citations (2)
| Title |
|---|
| 彭治汉 等: "《塑料工业手册 聚酰胺》", 31 December 2001 * |
| 杨鸣波 等: "《中国材料工程大典.第6卷.高分子材料工程(上)》", 31 March 2006 * |
Cited By (16)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN105949752A (en) * | 2016-05-11 | 2016-09-21 | 南京京锦元科技实业有限公司 | Glass fiber reinforced polyamide resin composite |
| CN108165001A (en) * | 2017-12-25 | 2018-06-15 | 江苏金发科技新材料有限公司 | The good appearance polyamide compoiste material of low water absorption |
| CN111205637A (en) * | 2018-11-21 | 2020-05-29 | 杭州本松新材料技术股份有限公司 | Heat stabilizer and composite material comprising the same |
| CN111205637B (en) * | 2018-11-21 | 2022-04-19 | 杭州本松新材料技术股份有限公司 | Heat stabilizer and composite material comprising the same |
| CN111363347B (en) * | 2020-03-19 | 2022-06-14 | 宁波创力液压机械制造有限公司 | Glass fiber reinforced nylon composite material and preparation method thereof |
| CN111363347A (en) * | 2020-03-19 | 2020-07-03 | 宁波创力液压机械制造有限公司 | Glass fiber reinforced nylon composite material and preparation method thereof |
| CN111892813A (en) * | 2020-07-28 | 2020-11-06 | 横店集团得邦工程塑料有限公司 | Low-odor reinforced toughened flame-retardant PA6 composite material and preparation method thereof |
| CN111892813B (en) * | 2020-07-28 | 2023-01-10 | 横店集团得邦工程塑料有限公司 | Low-odor reinforced toughened flame-retardant PA6 composite material and preparation method thereof |
| CN112266607A (en) * | 2020-09-30 | 2021-01-26 | 南京聚隆科技股份有限公司 | Heat-resistant glass fiber reinforced nylon material and preparation method thereof |
| CN112409668A (en) * | 2020-10-20 | 2021-02-26 | 浙江德裕科技有限公司 | Plastic window rail and preparation method thereof |
| CN112592577A (en) * | 2020-12-14 | 2021-04-02 | 山东明珠材料科技有限公司 | Continuous preparation method of glass fiber reinforced polyurethane section |
| CN113667300A (en) * | 2021-09-14 | 2021-11-19 | 四川恒领皓睿塑胶科技有限公司 | Glass fiber reinforced engineering plastic and preparation method thereof |
| CN113773458A (en) * | 2021-09-14 | 2021-12-10 | 安徽华超新材料科技有限公司 | Modification treatment method of chopped glass fibers |
| CN113667300B (en) * | 2021-09-14 | 2023-09-19 | 四川恒领皓睿塑胶科技有限公司 | Glass fiber reinforced engineering plastic and preparation method thereof |
| CN114507441A (en) * | 2021-12-24 | 2022-05-17 | 金发科技股份有限公司 | Polyamide composite material and preparation method and application thereof |
| CN114507439A (en) * | 2022-01-11 | 2022-05-17 | 宁波帅特龙集团有限公司 | Efficient antifouling nylon 6/glass fiber composite material and preparation method thereof |
Also Published As
| Publication number | Publication date |
|---|---|
| CN105176079B (en) | 2018-10-23 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN105176079B (en) | A kind of short glass fiber enhancing modified nylon material and preparation method thereof | |
| CN105860524B (en) | A kind of thermoplasticity low friction wearing composite material and preparation method thereof | |
| CN101230193B (en) | High-strength basalt fibre reinforced nylon composition and preparation method thereof | |
| CN106221204B (en) | Fiber glass reinforced polyamide composition and its preparation method and application | |
| CN107057339A (en) | A kind of activeness and quietness nylon material and its preparation method and application | |
| CN101983988B (en) | Polyamide 6 composite and preparation method thereof | |
| CN105062062A (en) | Halogen-free flame-retardant nylon composite material and preparation method thereof | |
| CN101338053B (en) | Polyolefine core tube and method for preparing same | |
| CN109456563B (en) | Special material for UHMWPE alloy compatibilization toughening modified polypropylene corrugated pipe and preparation method thereof | |
| CN113493606A (en) | Bio-based nylon composition for automobile pipelines and preparation method thereof | |
| CN101314672A (en) | High-gloss, low-smell, reinforced nylon composite material and preparation method thereof | |
| CN103709509A (en) | Expandable microsphere filling modified polypropylene composite material and preparation method thereof | |
| CN104725717A (en) | Internal-pressure-resistant polypropylene pipe and preparation method thereof | |
| CN101712792A (en) | Fire and heat resisting self-lubricating polycarbonate composite with nice appearance and preparation method thereof | |
| CN104802482A (en) | Three-layer co-extruded PP (polypropylene)/PE (polyethylene)/PP upward-blown film and preparation method thereof | |
| CN111040440A (en) | Low-density high-wear-resistance nylon composite material and preparation method and application thereof | |
| CN102040829B (en) | Glass fiber reinforced nylon material for high-speed railway system and preparation method thereof | |
| CN102796300A (en) | Ultra-high molecular weight polyethylene composite pipe, and raw materials and preparation method thereof | |
| WO2023040734A1 (en) | Wear-resistant high-impact polypropylene composition, preparation method therefor, and use thereof | |
| CN107541049B (en) | Graphene-continuous glass fiber reinforced halogen-free flame-retardant weather-resistant PPO/HIPS alloy material and preparation method thereof | |
| CN104072901B (en) | Underground modified PVC non-excavation special communication pipe and preparation method thereof | |
| CN101921452B (en) | Highly impact resistant polyformaldehyde compound and preparation method thereof | |
| CN105419210A (en) | Wear-resistant enhanced PPO/HIPS material and preparation method therefor | |
| CN106519661A (en) | Nylon PA66 material suitable for water-oil environment and preparation method thereof | |
| CN109971109A (en) | A kind of high sound-absorbing damping thermoplastic elastomer blend |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| C06 | Publication | ||
| PB01 | Publication | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| TA01 | Transfer of patent application right |
Effective date of registration: 20180808 Address after: 512200 No. 7 Jinling four road, Lechang industrial transfer industrial park, Lechang, Guangdong Applicant after: LECHANG WOFU NEW MATERIAL Co.,Ltd. Address before: 523000 Xinya Road, Daling Ya Village, dau Jiao Town, Dongguan, Guangdong Applicant before: DONGGUAN WOFU ENGINEERING PLASTIC SCIENCE & TECHNOLOGY Co.,Ltd. |
|
| TA01 | Transfer of patent application right | ||
| GR01 | Patent grant | ||
| GR01 | Patent grant | ||
| PE01 | Entry into force of the registration of the contract for pledge of patent right | ||
| PE01 | Entry into force of the registration of the contract for pledge of patent right |
Denomination of invention: Chopped-glass-fiber-reinforced nylon modified material and preparation method thereof Effective date of registration: 20200428 Granted publication date: 20181023 Pledgee: Guangdong Lechang Rural Commercial Bank Co.,Ltd. Pledgor: LECHANG WOFU NEW MATERIAL Co.,Ltd. Registration number: Y2020980001854 |
|
| PC01 | Cancellation of the registration of the contract for pledge of patent right |
Date of cancellation: 20210729 Granted publication date: 20181023 Pledgee: Guangdong Lechang Rural Commercial Bank Co.,Ltd. Pledgor: LECHANG WOFU NEW MATERIAL Co.,Ltd. Registration number: Y2020980001854 |
|
| PC01 | Cancellation of the registration of the contract for pledge of patent right | ||
| PE01 | Entry into force of the registration of the contract for pledge of patent right |
Denomination of invention: The invention relates to a short cut glass fiber reinforced nylon modified material and a preparation method thereof Effective date of registration: 20220516 Granted publication date: 20181023 Pledgee: Guangdong Lechang Rural Commercial Bank Co.,Ltd. Pledgor: LECHANG WOFU NEW MATERIAL Co.,Ltd. Registration number: Y2022980005627 |
|
| PE01 | Entry into force of the registration of the contract for pledge of patent right | ||
| PC01 | Cancellation of the registration of the contract for pledge of patent right |
Granted publication date: 20181023 Pledgee: Guangdong Lechang Rural Commercial Bank Co.,Ltd. Pledgor: LECHANG WOFU NEW MATERIAL Co.,Ltd. Registration number: Y2022980005627 |
|
| PC01 | Cancellation of the registration of the contract for pledge of patent right | ||
| PE01 | Entry into force of the registration of the contract for pledge of patent right |
Denomination of invention: The invention relates to a short cut glass fiber reinforced nylon modified material and a preparation method thereof Granted publication date: 20181023 Pledgee: Guangdong Lechang Rural Commercial Bank Co.,Ltd. Pledgor: LECHANG WOFU NEW MATERIAL Co.,Ltd. Registration number: Y2025980018475 |
|
| PE01 | Entry into force of the registration of the contract for pledge of patent right |